2008
DOI: 10.2514/1.33933
|View full text |Cite
|
Sign up to set email alerts
|

Bow Shock Wave Mitigation by Laser-Plasma Energy Addition in Hypersonic Flow

Abstract: Experimental results of bow shock wave mitigation by laser-plasma energy addition in a low-density Mach 7 hypersonic flow conducted in a shock tunnel are presented. A high-power pulsed CO 2 laser operating with 7 J of energy and 30 MW of peak power was used to generate the plasma ahead of a hemispherical model installed in the tunnel test section. The schlieren technique was used to visualize the time evolution of energy addition to the flow by laser-induced plasma and the interaction between this disturbed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…e experimental results showed that the peak pressure of the bow shock and the type IV shock interference was reduced by 40% and 30%, respectively. Minucci et al [8][9][10][11] conducted a single-pulse laser drag reduction experiment in a hypersonic shock wave tunnel. e air spike structure was observed using direct photography.…”
Section: Introductionmentioning
confidence: 99%
“…e experimental results showed that the peak pressure of the bow shock and the type IV shock interference was reduced by 40% and 30%, respectively. Minucci et al [8][9][10][11] conducted a single-pulse laser drag reduction experiment in a hypersonic shock wave tunnel. e air spike structure was observed using direct photography.…”
Section: Introductionmentioning
confidence: 99%
“…The advance of experimental studies previously performed at the IEAv, with respect to the addition of laser energy pulses to investigate vehicle drag and heat transfer (Minnuci et al, 2005, Oliveira, 2008a, 2008b, 2008c, Salvador et al, 2005, 2007, 2008, has shown the need of numerical analyses to obtain a better understanding of the phenomena generally observed and also to support new experiments. Th erefore, in this work, which focused on understanding the properties of an energized fl ow without the presence of bodies, it is presented a numerical investigation of a localized steady energy addition to highspeed airfl ows, by varying the energy deposition rate and the spatial dispersion for diff erent free stream airfl ow speeds (Fraile Jr., 2011).…”
Section: Introductionmentioning
confidence: 99%